2013
DOI: 10.4103/0970-9185.117107
|View full text |Cite
|
Sign up to set email alerts
|

Giant oral tumor in a child with malnutrition and sickle cell trait: Anesthetic challenges

Abstract: Pediatric oral tumors have always been challenging for the even most skilled anesthesiologists. The conventional method of awake intubation is not realistic in this age group. The management is to chart out a plan to intubate the child post induction. We describe successful management of a case of giant of ossifying fibroma in a child with sickle cell trait where non-conventional innovate approach helped us to secure the airway pre-operatively and avoid possible medical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Securing the airway in an awake child is not a very practical option. 1,2 Another approach that has been tried with limited success for awake intubation in the pediatric patient is the use of videolaryngoscopes. 3 However, a prerequisite of successful video laryngoscopy is the presence of adequate mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…Securing the airway in an awake child is not a very practical option. 1,2 Another approach that has been tried with limited success for awake intubation in the pediatric patient is the use of videolaryngoscopes. 3 However, a prerequisite of successful video laryngoscopy is the presence of adequate mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…Standard anesthesia monitors were attached to the patient in the operating room. Video laryngoscope-assisted orotracheal intubation under general anesthesia with maintenance of spontaneous respiration was planned, considering the anticipated difficulty of the airway [ 5 6 7 8 ]. The child was pre-oxygenated with 100% oxygen for 3 min.…”
Section: Case Reportmentioning
confidence: 99%
“…In a study to evaluate the benefits and safety of early versus late tracheostomy in traumatic spinal cord injury patients requiring mechanical ventilation, Romero et al .,[ 53 ] found that early tracheostomy following short orotracheal intubation is beneficial. It was found that early placement (before day 7 of mechanical ventilation) offers advantages for shortening of mechanical ventilation coupled with reducing ICU stay and lowering rates of complications, such as tracheal granulomas and concentric tracheal stenosis.…”
Section: Review Of Literaturementioning
confidence: 99%